DEVELOPMENT OF LOW COST PORTABLE ANTI-THEFT DEVICE (PATD) - Mohd Annuar, Khalil Azha; Mohd Ab Halim, Mohd Firdaus; Noordin, Aminurrashid; Ahmad, Suziana; Md Nawawi, Mohamad Riduwan (2012)
This paper discussed about the development of low cost Portable Anti-Theft Device (PATD) that able to reduce the issue in snatch-theft, property lost due to leaving it behind, misplace and to monitor the children movement in public area. This device consists of two parts that are the transmitter and receiver controlling circuit which communicate by RFID technology application. It also equipped with a high volume triggering alarm system that activates when the range between the transmitter and the receiver circuits reach a specific distance. It is hope that with this PATD can reduced the issues of theft and snatching crime as well as preventing from loss, injuries and missing.